2007
DOI: 10.3748/wjg.13.6037
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B viral infection in maintenance hemodialysis patients: A three year follow-up

Abstract: AIM:To observe the prevalence of hepatitis B virus (HBV) infection in maintenance hemodialysis patients. METHODS:Eighty-eight hemodialysis patients who had been receiving hemodialysis regularly for an average of 39.45 ± 7.57 (range from 36 to 49) mo were enrolled in this study. HBV markers were measured in these patients before hemodialysis and in 100 healthy controls by the chemiluminescent microparticle immunoassay (CMI) method in order to compare the incidence of HBV infection in hemodialysis patients versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[20] In this study positive anti-HBc was found in 44 patients (30.8%). Other studies by Gohar et al and Cendoroglo et al reported positive anti HBc in 51.8%, 55.7% of hemodialysis patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…[20] In this study positive anti-HBc was found in 44 patients (30.8%). Other studies by Gohar et al and Cendoroglo et al reported positive anti HBc in 51.8%, 55.7% of hemodialysis patients.…”
Section: Discussionmentioning
confidence: 64%
“…It has been suggested that the hemodialysis procedures lower HBV DNA level by various mechanisms: the clearance of HBV DNA by the dialysate, the entrapment of HBV DNA particles onto the membrane surface of dialyzers, and the production of cytokines and other substances during hemodialysis sessions. [20]…”
Section: Discussionmentioning
confidence: 99%
“…Because of cellular immune status disturbances, some authors believe that dialysis patients cannot terminate HBsAg production, a marker of viremia. A review of the literature found only five reported cases of HBsAg seroconversion among chronic carrier dialysis patients .…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrate different disease manifestations compared with healthy individuals and are far more likely to progress to a chronic carrier state . There are only a few reports of spontaneous HBsAg clearance in HD patients with chronic HBV infection . We report a case where a HD patient with longstanding chronic HBV infection spontaneously seroconverted temporally related to a persistent arteriovenous graft (AVG) infection and we offer a hypothesis for why this may have occurred.…”
mentioning
confidence: 95%
“…In dialysis patients the incidence and prevalence of HBV is high due to multiple parenteral exposures during dialysis and the immunosuppressed state associated with end stage renal disease [4, 16, 17]. Since 1982, HBV vaccination has been recommended for hemodialysis patients [18].…”
Section: Introductionmentioning
confidence: 99%